ICT in the educational context through scientific production in Spanish - Lorenzo-Lledó, Gonzalo; Lorenzo-Lledó, Alejandro; Lledó Carreres, Asunción (Revista General de Información y Documentación, 2019)
Various national and international educational reforms have been advocating the inclusion of technology as a significant resource in teaching-learning processes. The aim of this study is to carry out a bibliometric analysis of scientific production in Spanish on the inclusion of ICT in the educational context. The documents were searched in the ISI Web of Knowledge using the advanced search tab. After applying the search terms, 154 documents were obtained and analyzed according to a series of indicators. The results obtained indicate that the 2015-2017 period was the most prolix and the one that generated the greatest number of citations. The work carried out highlights the great importance of scientific journals in the publication and dissemination of research on ICTs in education.
Keywords: Inclusion; Technology; ISI web of Knowledge